Tick bite mimicking indeterminate cell histiocytosis. Issue 6 (21st September 2017) - Stringer, Thomas; Ghazi, Elizabeth; Alvarez del Manzano, Gilberto; Beasley, Jenna; Brinster, Nooshin; Oza, Vikash S.
Abstract: Ticks are a well‐known vector for viral, bacterial, and rickettsial infections, many of which are accompanied by cutaneous eruptions, but the bite itself can induce a spectrum of inflammatory reactions, including foreign body granuloma, tick bite alopecia, and cutaneous lymphoid hyperplasia. We describe the development of an indeterminate cell histiocytic infiltrate at the site of a tick bite. Although the etiology of intermediate cell histiocytosis is not well understood, this case raises the possibility that such infiltrates may represent an inflammatory reaction in some patients.